Analysis Of The Effect Of Product Quality on Consumer Purchase Decisions - Tandani, Alvionita (ADPEBI, 2022)
The purpose of this study was to determine the effect of product quality on consumer purchase decisions at PT. Karya Mandiri Pratama Plasindo Tanjung Morawa.The method used in this research is quantitative method. The type of research is quantitative data.The data collection technique used a questionnaires. The research population that will be used in this study is all customers who made purchases in the company total 239 consumers. Due to the total population used was 239 consumers, and using the Slovin formula obtained 150 respondents as samples. The analytical technique used is simple linear regression analysis and statistical tests, namely t-test (partial) using SPSS software (statistical package for the social sciences).The test results show that partially the product quality variable have a positive and significant effect on purchasing decisions where the influence given is 28.5%.The conclusion of this study is that partially, the product quality variable have a positive and significant effect on consumer purchase decisions at PT. Karya Mandiri Pratama Plasindo Tanjung Morawa. The purpose of this study was to determine the effect of product quality on consumer purchase decisions at PT. Karya Mandiri Pratama Plasindo Tanjung Morawa.The method used in this research is quantitative method. The type of research is quantitative data.The data collection technique used a questionnaires. The research population that will be used in this study is all customers who made purchases in the company total 239 consumers. Due to the total population used was 239 consumers, and using the Slovin formula obtained 150 respondents as samples. The analytical technique used is simple linear regression analysis and statistical tests, namely t-test (partial) using SPSS software (statistical package for the social sciences).The test results show that partially the product quality variable have a positive and significant effect on purchasing decisions where the influence given is 28.5%.The conclusion of this study is that partially, the product quality variable have a positive and significant effect on consumer purchase decisions at PT. Karya Mandiri Pratama Plasindo Tanjung Morawa.